Transarterial Chemoembolization – Status Quo in Germany - Niessen, C.; Wiggermann, P.; Velandia, C.; Stroszczynski, C.; Pereira, P. L. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2013)
Purpose: Against the background of the current preparation of the national disease management guideline for the diagnosis and treatment of hepatocellular carcinoma (HCC), the German Society for Interventional Radiology (DEGIR) launched a statewide survey in order to evaluate the current status of transarterial chemoembolization (TACE) in Germany.Materials and Methods: In April 2012 an e-mail questionnaire relating to TACE practices in patients with intermediate-stage HCC was sent to all chief physicians of interventional radiology departments in Germany that were members of DEGIR.Results: 96 questionnaires were completed and evaluated statistically. The most frequent combinations of embolic agents and cytotoxic drugs are drug-eluting beads combined with doxorubicin or epirubicin as well as lipiodol plus doxorubicin, epirubicin or cisplatin. 60 % of the interventionalists prefer superselective chemoembolization. In most cases more than one chemoembolization per patient is performed (95.5 %). The most common (77 %) time interval between two interventions ranges between one and two months.Conclusion: The results of this survey show the often stated criticism in Germany regarding the substantial differences in TACE protocols and highlight the importance of standards of practice for TACE in patients with HCC.Key Points:Citation Format:
Keywords: HCC; chemoembolization; interventional procedures